The Analysis of Elementary Mathematics Preservice Teachers' Spatial Orientation Skills with SOLO Model - ÖZDEMİR, AHMET ŞÜKRÜ (ANI YAYINCILIK, 2015)
Problem Statement: The SOLO model places responses provided by students on a certain level instead of placing students there themselves. SOLO taxonomy, including five sub-levels, is used for determining observed structures of learning outcomes in various disciplines and grade levels. On the other hand, the spatial orientation skill is the ability to visualize an object's view from a different perspective. A number of studies on examining preservice teachers' spatial abilities have been performed. In this study, elementary mathematics preservice teachers' spatial orientation skills as components of spatial skills were evaluated through the SOLO model in ways that are different from other researches. Purpose of the Study: The purpose of this study was to analyze the spatial orientation skills of elementary mathematics preservice teachers by using the SOLO model. In addition, responses of students who were at specified levels (low-middle-high) according to the Purdue Spatial Visualization Test scores were also classified. Preservice teachers' responses between different dimensions were also examined according to SOLO taxonomy. Method: The present research was a qualitative study and a case study method was employed. The sample of the study included junior elementary mathematics preservice teachers from a state university. Firstly, the Purdue Spatial Visualization Test was carried out with eighty-one students and then clinical interviews were conducted with six students according to three levels which were specified by looking at the results of the test in this study. The students' answers were placed into a suitable SOLO level according to an evaluation scale by analyzing each of the eight questions used in the Geometrical Achievement Test prepared by the researchers. Findings: Elementary mathematics preservice teachers' responses in a geometrical achievement test relating to spatial orientation skills were generally on a multistructural level according to SOLO taxonomy. Whereas the responses of preservice teachers who were on the low and middle levels were mostly on a multistructural level, the responses of the students on the high level were on a relational level. In addition, the responses of preservice teachers from two-dimension to three-dimension were mostly on a relational level and the responses from three-dimension to two-dimension were mostly on a multistructural level. Conclusion and Recommendations: Results obtained indicated that preservice teachers were not generally successful at combining their information within a consistent structure in terms of spatial orientation skills. They could only evaluate situations which were independent from each other separately. Therefore, students had surface learning rather than deep learning. Obtained data can be evaluated with a different taxonomy and a comparison could be made between these two models in further studies.
Keywords: SOLO taxonomy; spatial ability; clinical interview